Critical thinking puzzles - "Dispezio, Michael" (Goodwill publishing house: New Delhi, 2000)
Here are enough tough puzzles to test your mental powers for hours and hours. Try this never-ending array of puzzles, challenges, funky facts, things to build, weird riddles, and other conundrums. Some are old favorites that never fail to stump, others are totally new, but all promise hours of fun. Every one can be completed with a pencil, pen, or some inexpensive materials around the house.
Keywords: General works - Book